Assessing the Practices of Computer Teachers in Light of the Requirements of Formative Evaluation Strategies at the Intermediate Stage in the Kingdom of Saudi Arabia - Alshaikhi, Abdu Abdullah Saeed; Alshehri, Abdulelah Hamoud (Journal of Educational and Psychological Sciences, 2023)
The research aimed to assess the practices of computer teachers in the light of the requirements of the formative assessment strategies at the intermediate stage in the Kingdom of Saudi Arabia. The research used the descriptive method. The study population included all male and female computer teachers in the Education Department of Al-Leith Governorate. The study sample consisted of (54) male and (58) female teachers. The questionnaire was used as a tool. According to the findings of the research, the assessment of the practices of computer teachers’ practices in the light of the requirements of formative assessment strategies was generally "very significant," i.e., computer teachers use formative assessment tools. The research concluded that evaluation tools used by computer teachers were practical tests, computers to evaluate students, electronic tests, achievement files, and traditional written tests. The findings of their use of these strategies was as follows: the feedback strategy and the strategy of setting learning goals had a "very significant" degree of practice, while the performance-based evaluation strategy, the peer evaluation strategy, and the K.W.L.H strategy had a "significant" degree of practice. The research findings showed that there were no statistically significant differences at the level (0.05) with regard to the gender variable when practicing the strategy of setting learning goals and performance-based assessment, as well as the educational level variable. The research findings also revealed statistically significant differences at the level (0.05) with regard to the gender variable when practicing the feedback strategy, peer evaluation, and K.W.L.H, in favor of males. The research’s most significant recommendations were providing training programs for computer teachers to increase their use of the strategy of performance-based evaluation, peer evaluation, and K.W.L.H.